2001
DOI: 10.1054/bjoc.2000.1582
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of colorectal cancer risk and physical activity, diabetes, blood glucose and BMI: exploring the hyperinsulinaemia hypothesis

Abstract: A sedentary lifestyle, obesity, and a Westernized diet have been implicated in the aetiology of both colorectal cancer and non-insulin dependent diabetes mellitus, leading to the hypothesis that hyperinsulinaemia may promote colorectal cancer. We prospectively examined the association between colorectal cancer risk and factors related to insulin resistance and hyperinsulinaemia, including BMI, physical activity, diabetes mellitus, and blood glucose, in a cohort of 75 219 Norwegian men and women. Information on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
162
4
8

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(179 citation statements)
references
References 29 publications
(27 reference statements)
5
162
4
8
Order By: Relevance
“…Campbell et al (2007) concluded that obesity is associated with colon and rectal cancer only in women but not men. Nilsen and Vatten (2001) study revealed that no association was found between BMI and CRC neither in males nor females of the study. However, the lower BMI among cases which has been detected in this study may reflect the effect of chemotherapy and other therpies that were used to treat cancer patients (DobrilaDintinjana et al, 2012).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Campbell et al (2007) concluded that obesity is associated with colon and rectal cancer only in women but not men. Nilsen and Vatten (2001) study revealed that no association was found between BMI and CRC neither in males nor females of the study. However, the lower BMI among cases which has been detected in this study may reflect the effect of chemotherapy and other therpies that were used to treat cancer patients (DobrilaDintinjana et al, 2012).…”
Section: Discussioncontrasting
confidence: 52%
“…Lifestyle characterized by low physical activity may result in a positive energy balance and weight gain (Marchand et al, 1997). The role of physical inactivity and obesity in CRC prevention have been shown CRC in several studies (Whittemore et al, 1990;Marchand et al, 1997;Nilsen and Vatten, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Findings from available epidemiologic studies of women have been less conclusive, with results from several prospective studies observing no association [6,8,15,32] and others reporting statistically nonsignificant risk reductions [33,34]. Few studies found a statistically significant inverse association between physical activity and colorectal cancer in women [13,16,35].…”
Section: Discussionmentioning
confidence: 99%
“…Breast, colon, uterine, and ovarian cancer incidence have also been shown to increase with BMI (19,20). Obesity is associated with comorbidities that include type 2 diabetes, hyperlipidemia, HTN, OSA, stroke, asthma, and back and lower extremity weight-bearing degenerative problems (2,14,(21)(22)(23).…”
Section: Bmi Criteriamentioning
confidence: 99%